ANALISIS FAKTOR DAN USULAN PERBAIKAN KUALITAS HASIL CETAK KORAN INDUSTRI GRAFIKA - Yusnia Sinambela (JUITECH: Jurnal Ilmiah Fakultas Teknik Universitas Quality, 2019)
PT. X as a company engaged in the printing and publishing industry. In carrying out its business activities the company has implemented a production quality control system. Various quality control programs are carried out by the company so as to produce good products and in accordance with established quality standards. But in reality there are still products that are of poor quality. The damaged product is then rejected (separated from the product that falls into good criteria) and will be resold to other parties at a price lower than the general price. This is certainly a loss for the company because it results in a waste of production, especially if the damaged product exceeds the tolerance limit set by the company. Based on the results of the study obtained a large defect in printout Newspapers include blurred colors, not registers and cut. By using a quality analysis using a Fish Bone Diagram, the factors that generally affect print quality are human, material, method, environment and machine